Wing membrane and fur samples as reliable biological matrices to measure bioaccumulation of metals and metalloids in bats. (October 2019) - Mina, Rúben; Alves, Joana; Alves da Silva, António; Natal-da-Luz, Tiago; Cabral, João A.; Barros, Paulo; Topping, Christopher J.; Sousa, José Paulo
Abstract: There is a growing conservation concern about the possible consequences of environmental contamination in the health of bat communities. Most studies on the effects of contaminants in bats have been focused on organic contaminants, and the consequences of bat exposure to metals and metalloids remain largely unknown. The aim of this study was to evaluate the suitability of external biological matrices (fur and wing membrane) for the assessment of exposure and bioaccumulation of metals in bats. The concentration of arsenic, cadmium, cobalt, chromium, copper, manganese, nickel, lead, selenium and zinc was measured in internal organs (liver, heart, brain), internal (bone) and external tissues (wing membrane, fur) collected from bat carcasses of four species ( Hypsugo savii, Nyctalus leisleri, Pipistrellus pipistrellus, Pipistrellus pygmaeus ) obtained in windfarm mortality searches. With the exception of zinc ( P = 0.223), the results showed significant differences between the concentrations of metals in the analyzed tissues for all metals ( P < 0.05). Significant differences were also found between organs/tissues ( P < 0.001), metals ( P < 0.001) and a significant interaction between organs/tissues and metals was found ( P < 0.001). Despite these results, the patterns in terms of metal accumulation were similar for all samples. Depending on the metal, the organ/tissue that showed the highest concentrations varied, but fur and wing had the highest concentrations for most metals. The variability obtained in terms of metal concentrations in different tissues highlights the need to define standardized methods capable of being applied in monitoring bat populations worldwide. The results indicate that wing membrane and fur, biological matrices that may be collected from living bats, yield reliable results and may be useful for studies on bats ecotoxicology, coupled to a standardized protocol for large-scale investigation of metal accumulation. Graphical abstract: Image 1 Highlights: Internal and external samples were used to assess metal accumulation in bats. Metal concentrations measured depended on the tissue/organ analyzed. Wing membrane and fur had the highest metal concentrations for most metals. Wing membrane can be a proxy for metal concentrations in internal organs. External biological matrices are the best option for studies on wildlife ecotoxicology. Abstract : Wing membrane and fur are reliable biological matrices for studies on bats ecotoxicology, being useful to measure bat's exposure to metals/metalloids.